Pre-exposition to polycyclic aromatic hydrocarbons (PAHs) enhance biofilm formation and hydrocarbon removal by native multi-species consortium - Isaac, Paula (2017)
In this work, a biofilm-mediated removal of polyaromatic hydrocarbons (PAHs) was proposed. PAHs are toxic and persistent contaminants from petroleum industry, dispersed on water, soils, air and sediments. The removal capabilities of C15 mixed culture of four indigenous strains of Pseudomonas and actinobacteria were successfully corroborated in a previous work. Results showed an interesting removal behavior of planktonic C15 consortium, with degradation capabilities notably enhanced when comparing with pure cultures. In the work reported in this paper, biofilm formation was evaluated in pure cultures and C15 defined consortium in order to propose a biofilm mediated immobilization strategy for bioremediation. Interestingly, a notable enhancement (approx. 180%) in biofilm formation was observed after mixing the four species of C15 compared with pure cultures. Phenanthrene and pyrene also stimulated biofilm arrangement and biofilm-immobilized microorganisms demonstrated a hydrocarbon removal significantly higher than planktonic cells. Maximal removal values were 100% for phenanthrene and 78% for pyrene, after 7 days incubation. The biodegradation assay was divided into two stages: biofilm formation and hydrocarbon removal. The importance of PAHs presence during biofilm formation was evaluated. Although no differences in biofilm structure were observed, bioemulsifier production was enhanced and removal was accelerated when phenanthrene and pyrene were added during biofilm formation stage. Even though more experiments must be conducted, considering the coexistence of Pseudomonas and actinobacteria groups during biodegradation and the improvement of removal performance, interspecies beneficial interactions could be suspected in this native multi-species biofilm.